Determination of reference intervals of hemogram with advanced clinical parameters by indirect method on Sysmex XN-1000 - Bildirici, Mehmet Akif; Gülten, Sedat; Çalışgan, Neslihan Cihan (Walter de Gruyter GmbH, 2023)
Abstract Objectives The reference interval is the primary tool used to interpret laboratory test results. Each laboratory should determine reference intervals (RIs) that reflect their population. In this study, it was aimed to determine the RIs of hemogram routine and advanced clinical test parameters for our hospital and region by indirect method and to compare these calculated RIs with the limits recommended by the current manufacturer and the literature. Methods The hemogram results of patients aged 18–65 years who applied to Kastamonu Training and Research Hospital between July 2020 and June 2022, were included in the study. Hemogram analyzes were performed on Sysmex XN-1000 (Kobe, Japan) hematology auto analyzers. The RIs were determined by indirect method from the obtained data using the non-parametric percentage estimation method. Harris-Boyd method was used to decide on subgroup separation based on gender. Results All parameters had non-parametric distribution. RBC, HGB, HCT, MCH, MCHC, PLT, RDW-CV, RDW-SD, PCT, monocytes count, eosinophils count, monocytes % and macroR parameters which required gender-spesific RIs were determined separately for genders. Conclusions When the results are evaluated, it shows that the manufacturer’s recommendations together with the studies in the literature do not fully reflect the RIs of our population. Therefore, it is very important for each laboratory to determine its own RIs due to the differences in population, diet, technical equipment used and reference group. In addition, we think that our study will make a significant contribution to the literature, since there is insufficient data in the literature on RIs for advanced clinical parameters.
Keywords: hemogram; sysmex xn-1000; QD415-436; indirect reference intervals; advanced clinical parameters; Biochemistry; 3. Good health